Editorial: World’s oceans: opportunities and challenges looking under the sea - Hughes, Melanie Hebe (2024)
The oceans are home to a vast biodiversity below their surface, offering innumerableopportunities that remain mostly untapped. In recent years, marine organisms have drawnincreasing interest as a renewable and sustainable source of pharmacological, food andcosmetic bioactive compounds (Ebrahimi et al., 2023). In addition, the great biodiversity oforganisms, from invertebrates to algae, and the interactions among them, are being studiedin search of sources of renewable energy (Borowitzka and Moheimani, 2013), sewagetreatment mechanisms (Sutherland and Ralph, 2019), aquaculture techniques (Ma andQin, 2023), among other aspects. However, the sustainable use of these resources also drawsenormous challenges that must be overcome. The numerous pollutants found in marineecosystems (such as microplastics and nanoparticles, heavy metals and nutrients), highpopulation densities in many coastal areas and poor public policies addressing these issues,all pose a threat to the unique, resource-rich coastal and marine biodiversity (Gobas andMorrison, 2000; Cloern, 2001; Andrady, 2011; Holmes et al., 2012).This Research Topic focuses on the emerging opportunities and challenges related tothe utilization of marine resources, with a view to coordinating efforts towards a sustainabledevelopment. The articles published in this Topic, reveal the interconnected roles of marineorganisms, including diatoms, macroalgae and polychaetes, and their potential for nutrientrecycling and sustainable aquaculture practices, underscoring the complex dynamics ofmarine ecosystems in the face of anthropogenic pressures and climate change.